2017
DOI: 10.5812/ijp.9593
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Diagnostic Value of Neutrophil to Lymphocyte Ratio in Pediatric Appendicitis Cases

Abstract: Background: Abdominal pain is one of the most common complaints and appendicitis is the most common etiology of acute abdominal pain in the emergency departments for pediatric population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
3
1
1
Order By: Relevance
“…The estimated sensitivity of the NLR reported is 63-90% and specificity, 57-89%. 2,4,6,8,10,13,26,27 In our study, 81% of cases with AA developed complicated appendicitis; such prevalence is higher than that reported in previous studies. A recent systematic review reported complicated appendicitis in 35% of 2782 appendectomies performed in pediatric patients.…”
Section: Discussioncontrasting
confidence: 66%
“…The estimated sensitivity of the NLR reported is 63-90% and specificity, 57-89%. 2,4,6,8,10,13,26,27 In our study, 81% of cases with AA developed complicated appendicitis; such prevalence is higher than that reported in previous studies. A recent systematic review reported complicated appendicitis in 35% of 2782 appendectomies performed in pediatric patients.…”
Section: Discussioncontrasting
confidence: 66%
“…This retrospective study from Turkey on 628 patients with AA and 30 in non-AA groups showed that the MPV values did not significantly differ between the two groups ( p = 0.498) [ 15 ]. The study also investigated the role of WBC, neutrophil count, lymphocyte count, hemoglobin, hematocrit, platelet count, red cell distribution width (RDW), and CRP.…”
Section: Resultsmentioning
confidence: 99%
“…The surgeon has a hard choice between waiting to perform surgery until a complete diagnosis and operating soon after diagnosis to elude complications [ 17 , 18 ]. The preoperative difference between complicated and uncomplicated appendicitis may be difficult [ 19 , 20 ]. Clinical examination identifying signs of peritoneal irritation and imaging studies showing signs of complicated conditions such as intra-abdominal abscesses, pneumoperitoneum, or free intra-abdominal liquid is useful, but the definitive diagnosis of perforated appendicitis still requires surgery and histological diagnosis [ 3 , 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%